Effect of inlet air velocity on air-water harvester machines using one and two evaporator with 1.5 PK compressor power - M.A. Vayasqi; Y.A. Padang; M. Mirmanto (Dinamika Teknik Mesin, 2025)
During the dry season, clean water crisis often occurs in various parts of Indonesia. As a result, clean potable water is difficult to obtain. Therefore, this research uses an air-water harvester machine, because this machine can be used anywhere as long as there is a source of electricity at that location. This study aims to determine the effect of inlet air velocity on air-water harvester machines using one and two evaporators with 1.5 PK rotary compressor power on water mass and total heat transfer rate. The method used in this research is the experimental method, with variations in inlet air velocity of 0 m/s, 1.5 m/s and 3 m/s, using one and two split AC fin type evaporators each with a capacity of 0.5 PK, with a pipe diameter of 7.65 mm. The refrigerant used is R32. The study was conducted from 09:00 to 16:00, for 18 days, 7 hours per day. The results showed that the higher the air velocity used and the increase in the number of evaporators, can increase the mass of water and the heat transfer rate obtained. The highest mass of water and heat transfer rate obtained in this study is in the air velocity variation of 3 m/s using two evaporators, which is 4.073 kg of water mass for 7 hours and a total heat transfer rate of 1375.09 W.